Position‐track‐time three‐dimensional network model‐based improvement for high‐speed rail scheduling and operation. (25th August 2022) - Wang, Jin; Ai, Chengbo; Chen, Yongjun; A, Runa; Wang, Weidong; Qiu, Shi
Abstract: The train timetable and station operation plan play a critical role in the high‐speed railway (HSR) planning and management. The existing hierarchical optimization methods for the planning process of the HSR would affect the efficiency of train schedules and are often difficult to achieve an optimized scheme. This paper proposes a position‐track‐time three‐dimensional network, which describes the process of train operations in sections and stations at a macroscopic scale, while the track infrastructure including the position of insulation joints in stations are modeled microscopically. The modeled train running times and dwell times are based on standard timetable design values given in full minutes by the China Railway Corporation, while the interlocking times and minimum headway times are not specified explicitly. The problem is formulated as a large‐scale 0–1 linear integer programming model, which is solved using an extended branch‐and‐price algorithm. The effectiveness and precision of the model are verified through a real‐world case study on the Beijing–Shanghai HSR line. The results indicate that the proposed model can effectively improve the line capacity by 17.2% while ensuring that there is no conflict between train operations in sections and stations.